PENGARUH PERENCANAAN PAJAK DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN JASA KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDOENSIA PERIODE 2009 – 2013 - Muhammad Hidayat; Muhammad Imam Akbar Hairi (Universitas Indo Global Mandiri)
The aim of this research is to know the influence of tax planning and intellectual capital on firm value. The objects of this research are financial sector companies at Indonesian Stock Exchange. Multiple Linier Regression is applied to analyze the data. The result show that tax planning has negative significant influence on firm value, intellectual capital has positive significant on firm value, tax planning and intellectual capital simultaneously have positive significant on firm value.Key word: tax planning, intellectual capital, firm value.